Interfacial shear strength of carbon nanotubes based hybrid composites: effect of loading rate (Fracture and Structural Integrity, 2019)
Interfacial interaction is investigated between the two basic constituents in carbon fiber reinforced plastics (CFRPs). Efforts have been made to quantify the interfacial shear strength (IFSS) between individual carbon fiber (CF) and epoxy matrix in CFRPs by performing single fiber micro-droplet debond test. Initially, IFSS of the epoxy composites reinforced with unsized carbon fiber (HCF) is assessed. Study is then extended to assess the IFSS of carbon nanotubes (CNTs) based CFRP hybrid composites. The hybrid composites are prepared by reinforcing epoxy matrix with CNT grafted carbon fibers (CNTCF). The versatile, simple and time effective method of chemical vapor deposition is used to synthesize CNTs directly on the surface of CF. IFSS is found to enhance after the inclusion of grafted CNTs in CFRP composites. Keeping in mind the application view point of CFRPs to put up with varying loads, effect of loading rate on the IFSS of CFRPs is also examined. To this end, both HCF/epoxy and CNTCF/epoxy composites are debonded at cross-head rates varying by two orders of magnitude and IFSS is compared. Finally, scanning electron microscopy of debonded fibers is carried out to understand the interfacial failure mechanism in various composites.
Keywords: Carbon Fiber; CFRP; CNTs; Epoxy; IFSS; Microbond